IMPLEMENTASI MOTIF SOSIAL DAN MOTIF RELIGIUS TERHADAP KINERJA (PERPEKTIF MAQASHID AL-SYARI’ AH ) - Prajawati, Maretha Ika (IQTISHODUNA, 2015)
Islamic bank as a business entity is required not only as a company that looking for a profit, but alsoperform the function and purpose as a Shariah entity that based on the concept of Maqasid al-Shariah. Everymuamalah or economic activity must be executed in accordance with the values and Islamic principles thatprovide flexibility, dynamism and creativity decision making. For companies, the welfare of shareholders,stakeholders and social environment are the goals that must be achieved, so that Maqasid al-Shariah becomea reference in making strategic decisions related to financial and investment aspects. In achieving corporateobjectives to improve performance, companies are encouraged to take action in the social dimension, namelythe concern for others by implementing of social responsibility programs and payment of zakat as religiouslymotivated companies in order to improve the performance of the company. The results showed that socialmotives are reflected in social responsibility influence the performance of Islamic banking improvement, aswell as religious motive reflected by payment of zakat effect to improved performance of Islamic banking.